The MLE of the Parameters of a Discrete Competitive System Subject to Environmental Noise - Huili Xiang; Zhijun Liu (Discrete Dynamics in Nature and Society)
A randomized discrete competitive system is investigated and the maximum likelihood estimation (MLE) of the parameters of the system is obtained. Also, a corresponding numerical simulation is offered to support our theoretical results.